EXPLORING POST-COMPRESSION PARAMETERS IN MARKETED VILDAGLIPTIN TABLETS - Siva, P Krishna (Journal of Global Pharma Technology, 2024)
This study investigates the post-compression parameters of tablets produced by five prominent pharmaceutical brands. Tablets play a crucial role in drug delivery, and their quality is essential for ensuring therapeutic efficacy. The post-compression phase is a critical step in tablet manufacturing, influencing key parameters such as weight variation, hardness, friability, and disintegration. This research aims to assess and compare these parameters for tablets from five selected brands, confirming their adherence to quality standards. The tablets from Brand A, Brand B, Brand C, Brand D, and Brand E underwent a rigorous testing protocol to evaluate hardness using a calibrated hardness tester, friability through Roche friabilator, and disintegration employing a disintegration tester. The study utilized standardized testing methods to ensure consistency and reliability across all assessments. Results revealed that all five brands successfully met benchmarks for weight variation, hardness, friability, and disintegration time. The tablets demonstrated robust mechanical strength, minimal friability, and prompt disintegration of active pharmaceutical ingredients. Keywords: Post-compression, Hardness, Friability, Disintegration.